Expository Science: Forms and Functions of Popularisation
XIV, 294 p.
Keywords: The prevailing view of scientific popularization, both within academic circles and beyond, affirms that its objectives and procedures are unrelated to tasks of cognitive development and that its pertinence is by and large restricted to the lay public. Consistent with this view, popularization is frequently portrayed as a logical and hence inescapable consequence of a culture dominated by science-based products and procedures and by a scientistic ideology. On another level, it is depicted as a quasi-political device for chan nelling the energies of the general public along predetermined paths; examples of this are the nineteenth-century Industrial Revolution and the U. S. -Soviet space race. Alternatively, scientific popularization is described as a carefully contrived plan which enables scientists or their spokesmen to allege that scientific learn ing is equitably shared by scientists and non-scientists alike. This manoeuvre is intended to weaken the claims of anti-scientific protesters that scientists monopolize knowledge as a means of sustaining their social privileges. Pop ularization is also sometimes presented as a psychological crutch. This, in an era of increasing scientific specialisation, permits the researchers involved to believe that by transcending the boundaries of their narrow fields, their endeavours assume a degree of general cognitive importance and even extra scientific relevance. Regardless of the particular thrust of these different analyses it is important to point out that all are predicated on the tacit presupposition that scientific popularization belongs essentially to the realm of non-science, or only concerns the periphery of scientific activity.